Bahasa Jawa dalam Orasi Politik Ganjar Pranowo dalam Kanal Youtube SAHABAT GANJAR - Nur Ikhsan; Prembayun Miji Lestari (Kawruh: Journal of Language Education, Literature and Local Culture, 2025)
Language in the political sphere has an important role in building an image and communication with the community, especially the use of regional languages such as Javanese. Studies on language variations used by political figures when giving speeches or campaigning in certain areas are still limited. This research focuses on the use of language variation in terms of speakers and influencing factors in political speeches conducted by Ganjar Pranowo at the grand campaign in Kendal and Yogyakarta. The type of research used is descriptive qualitative by using observation analysis technique, observing and recording data transcripts and analyzed using SBLC (Simak Bebas Libat Cakap) data collection technique. The research data is in the form of phrases, words, and sentences that contain a variety of language variations with data sources in the form of videos uploaded on the YouTube platform under the channel name Sahabat Ganjar. From the results of the analysis that has been done, it can be concluded that there are several types of language variations in terms of speakers in Ganjar Pranowo's communication, among others; in terms of speakers in the form of 18 idiolects, 12 dialects, 3 sociolects and no data found in the classification of chronolect varieties. Factors that influence the use of language variation in terms of speakers include internal factors and external factors with the acquisition of 23 language variations caused by internal factors and 12 external factors.